Dinamika dan Konstruksi Sosial System Kekerabatan Masyarakat Banten - Shofwan, Tengku Muhammad Faza; S, Safei; Sujana, Maftuh (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The kinship system is an important part of the life of the people of Banten, because it is the basis of the relationship between family members and the community. This study reviews how the kinship system in Banten was formed and developed along with the changing times. In daily life, the people of Banten still uphold values such as helping each other, respecting parents, and maintaining family harmony. However, the influence of modernization such as education, technology, and lifestyle has only begun to shift the way the younger generation views family and social relationships. This study uses a qualitative approach with observation and interviews as the main method. The results show that the kinship system in Banten is flexible and able to adapt without losing the core values of local culture. This study is expected to be an initial reference for anyone who wants to understand more deeply about the social and cultural life of the people of Banten.